2018
DOI: 10.1002/cne.24448
|View full text |Cite
|
Sign up to set email alerts
|

GABA‐like immunoreactivity in Biomphalaria: Colocalization with tyrosine hydroxylase‐like immunoreactivity in the feeding motor systems of panpulmonate snails

Abstract: The simpler nervous systems of certain invertebrates provide opportunities to examine colocalized classical neurotransmitters in the context of identified neurons and well defined neural circuits. This study examined the distribution of γ-aminobutyric acid-like immunoreactivity (GABAli) in the nervous system of the panpulmonates Biomphalaria glabrata and Biomphalaria alexandrina, major intermediate hosts for intestinal schistosomiasis. GABAli neurons were localized in the cerebral, pedal, and buccal ganglia of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 86 publications
1
14
0
Order By: Relevance
“…In addition, GABA and possibly glycine might be expected to colocalize with VGAT (Chaudhry et al, ; McIntire, Reimer, Schuske, Edwards, & Jorgensen, ), but results obtained using antibodies against GABA and glycine produced different staining patterns from that observed for VGAT/KLH‐LIR (see Supporting Info. ); staining patterns produced by GABA were consistent with those in B. glabrata (Vaasjo et al, ) and shared similarities with other species (Díaz‐Ríos, Suess, & Miller, ; Gunaratne et al, ).…”
Section: Resultssupporting
confidence: 78%
“…In addition, GABA and possibly glycine might be expected to colocalize with VGAT (Chaudhry et al, ; McIntire, Reimer, Schuske, Edwards, & Jorgensen, ), but results obtained using antibodies against GABA and glycine produced different staining patterns from that observed for VGAT/KLH‐LIR (see Supporting Info. ); staining patterns produced by GABA were consistent with those in B. glabrata (Vaasjo et al, ) and shared similarities with other species (Díaz‐Ríos, Suess, & Miller, ; Gunaratne et al, ).…”
Section: Resultssupporting
confidence: 78%
“…To test whether PRNs account for behavioral selection in vivo, we first identified the transmitter used by these cells to drive egestion. Previous mapping studies have revealed a single pair of unidentified dopaminergic neurons on the ventral surface of the buccal ganglia ( 20 , 21 ), and we hypothesized that these might be PRNs. Electrophysiology and double-labeling experiments using Alexa Fluor and dopamine antibody staining supported this idea ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Fronczek, Lammers, Balesar, Unmehopa, and Swaab () verified the specificity of the anti‐orexin antiserum by performing a dot blot test against a panel of 22 compounds, with only the orexin‐A well resulting in labeling. Vaasjo et al () report that the anti‐TH antibody used specifically labels neurons that are otherwise identified with several independent catecholaminergic markers, and Yew et al () performed an adsorption test with TH to show its specificity.…”
Section: Methodsmentioning
confidence: 99%